2004
DOI: 10.1007/s00428-004-1102-5
|View full text |Cite
|
Sign up to set email alerts
|

A benign neoplasm with histopathological features of both schwannoma and retiform perineurioma (benign schwannoma-perineurioma): a report of six cases of a distinctive soft tissue tumor with a predilection for the fingers

Abstract: We present six cases of a distinctive soft tissue tumor which occurred in five women and one man. None of the patients had signs of neurofibromatosis. All tumors occurred on the fingers ( n=5) or the thenar eminence of the hand ( n=1). The mean age of the patients was 33 years. The tumors were 1-2.5 cm in diameter (mean size 1.6 cm). Three patients with follow-up were without signs of recurrence or metastasis. Microscopically the lesions were nonencapsulated and featured a multilobular architecture and both my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
55
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 39 publications
3
55
1
Order By: Relevance
“…Although perineurioma has been first described in 1978 [19], it still represents a poorly recognised neoplasm in the spectrum of peripheral nerve sheath tumours [25], and, especially, examples of unusual histological variants cause considerable diagnostic problems and may be mistaken for different or more aggressive soft tissue tumours. Interestingly, rare examples of benign peripheral nerve sheath tumours showing a combination of perineurioma and schwannoma as well as of perineurioma and neurofibroma have been reported most recently [18,23]. In this review one case each of reticular and plexiform perineurioma is reported, and a review of perineurial neoplasms of skin and soft tissues is given.…”
Section: Introductionmentioning
confidence: 94%
“…Although perineurioma has been first described in 1978 [19], it still represents a poorly recognised neoplasm in the spectrum of peripheral nerve sheath tumours [25], and, especially, examples of unusual histological variants cause considerable diagnostic problems and may be mistaken for different or more aggressive soft tissue tumours. Interestingly, rare examples of benign peripheral nerve sheath tumours showing a combination of perineurioma and schwannoma as well as of perineurioma and neurofibroma have been reported most recently [18,23]. In this review one case each of reticular and plexiform perineurioma is reported, and a review of perineurial neoplasms of skin and soft tissues is given.…”
Section: Introductionmentioning
confidence: 94%
“…As previously noted, at the immunohistochemical and ultrastructural level, perineurial cells may participate substantially in the formation of peripheral nerve sheath tumors, both neurofibromas [5] and schwannomas [6,7]. On the other hand, perineuriomas are entirely perineurial in cell composition.…”
Section: Discussionmentioning
confidence: 89%
“…These include Schwann cells [2], and fibroblasts [3], both components of endoneurium, and even arachnoid cap cells [4]. Microscopically, obvious perineurial cells with typical immunohistochemical and ultrastructural features may be a conspicuous component of so-called mixed or ''hybrid'' peripheral nerve tumors, including neurofibroma [5] and schwannoma [6,7]. Perineurial cells have also been encountered in a rare example of multiple granular cell tumors [8].…”
Section: Introductionmentioning
confidence: 97%
“…1,2 Complicating in differential diagnosis is the observation of collision tumors like schwannoma and perineurinoma. 6 …”
Section: Discussionmentioning
confidence: 99%